Health Care Development Model Of COVID-19 Prevention For Conscript Soldiers in Krit Siwara Military Camp Sakon Nakhon Province - Boriboon, Ammarat; Raksilp , Monthicha; Songserm, Nopparat (Journal of The Royal Thai Army Nurses, 2023)
The aims of this action research are to: 1. Study the context of COVID-19 prevention for soldiers in the Krit Siwara Camp.2. Develop a COVID-19 prevention model.3. Study the effectiveness of the COVID-19 prevention model. The study involves 30 conscript soldiers aged between 18-26 years, using a healthcare development model of COVID-19 prevention that was consisting of activities 1.education, 2. a disease prevention practice, 3.reverse demonstration. This action research uses questionnaires and behavioural observations, and data is processed using content analysis and descriptive statistics. Results from the analyzed data show that: 1. The context of the conscript soldier is crowded and separated by regiment, resulting in a high risk of COVID-19 spread. 2. A healthcare model of COVID-19 prevention was developed and applied to the conscript soldiers through education and reverse demonstration by the health team. 3. The mean scores of knowledge, behaviours, motivation and social support for COVID-19 prevention were found to be statistically significant at the 0.05 level. These results indicated that the healthcare prevention model for COVID-19 helped soldiers to have a better awareness of the prevention of COVID-19 and should continue to be expanded to other units.